Glycaemic variability and risk of adverse cardiovascular events in acute coronary syndrome. (4th November 2022) - Zhang, Lei; Li, Feng; Liu, Huan-Huan; Zhang, Zhi-Yuan; Yang, Fan; Qian, Ling-Ling; Wang, Ru-Xing
Objective: The relationship between different glycaemic variability (GV) indexes and adverse cardiovascular outcomes is not well understood. This study aims to determine whether GV is related to the occurrence of adverse cardiovascular events in patients with acute coronary syndrome (ACS). Methods: PubMed, EMBASE, and Web of Science were comprehensively searched from the establishment of databases to 29 June 2022. The relationship between two important GV indexes, including the mean amplitude of glycemic excursion (MAGE) and standard deviation (SD), and the adverse cardiovascular events in ACS patients were evaluated, respectively. Results: A total of 11 studies with 3709 ACS patients were included. Pooled results showed that patients with higher GV had significantly increased risk of adverse cardiovascular events, including MAGE (relative risk [RR] = 1.76, 95% CI: 1.40 to 2.22, p < 0.001, I 2 = 25%) and SD (RR = 2.14, 95% CI: 1.73 to 2.66, p < 0.001, I 2 = 0%). Conclusions: Increased GV is related to the poor prognosis in patients with ACS. Additionally, more well-designed studies comparing different indicators of GV with adverse cardiovascular events in ACS patients are still warranted.